Analysis of the Implementation of Project-Based Learning Methods in Teaching English Speaking Skills - Siminto Siminto; Mike Nurmalia Sari; Nanda Pambudi; Devi Nurhastuti; Henny Merizawati (Departement of Mathematics Education, 2024)
In the dynamic landscape of education, effective teaching methods for developing English speaking skills continue to evolve. This article analyzes the implementation of Project-Based Learning (PBL) in the context of teaching English speaking skills, aiming to evaluate its impact on language learners and provide insights into the effectiveness of this teaching strategy. We explore the theoretical foundations of PBL, analyze its application in language classrooms, and investigate the outcomes of its implementation in the context of English language acquisition.